PERMAINAN ALEGORI DALAM NOVEL O KARYA EKA KURNIAWAN - Fadhilla, Indah (UI Scholars Hub, 2023)
Fables typically attach human attributes to animal characters to convey moral messages and teachings, but a number of modern authors use animal characters in their literary works to criticize current sociocultural phenomena. One famous literary work that contains many forms of allegory about relationships between human and animal characters is O, a novel by Eka Kurniawan. Allegories in O are used to exhibit contradictions between humans and animals. Animal characters are presented as possessing human traits, bringing up the idea that animals can become ideal human beings (the concept of “being human”). Meanwhile, human characters are presented as possessing animal instincts, bringing up the idea that humans can become animals (the concept of “becoming animal”). The author also explores humanitarian issues by presenting animal characters who turn out to be more humane than humans.